Cholesterol and fatty acid composition of lamb serum and offal as affected by alfalfa and concentrate - Cerci, Ibrahim H.; Ciftci, Mehmet; Bahsi, Muammer; Kilinc, Unal (Univ Zagreb Vet Faculty, 2011)
This study was conducted to investigate the effects of fresh, ensiled and dried alfalfa on the fatty acid composition and cholesterol level of the serum, liver, kidney and spleen samples in yearling sheep. Forty Akkaraman lambs, 4 months of age, with an average body weight of 21 kg were used in the study. All diets were formulated to be isonitrogenous and isoenergetic. The lambs were divided into four groups according to feed: wheat straw as roughage (Control group, C); fresh alfalfa as roughage (AF group); ensiled alfalfa (AS group); and dried alfalfa (AD group). The alfalfa group had lower saturated fatty acid (SFA) and higher polyunsaturated fatty acid (PUFA) contents than the wheat straw group. In parallel, SFA concentrations in the serum and offal (liver, kidney and spleen) were significantly higher in the controls, whereas the highest PUFA amounts were recorded in lambs fed with fresh alfalfa. Serum and offal proportions of omega 3 and omega 6 fatty acids significantly increased except in serum omega 3 content of lambs fed with alfalfa. However, the cholesterol level decreased in all groups given alfalfa. In conclusion, the results of this study suggest that alfalfa consumption causes a significant decrease in cholesterol levels and a significant increase in PUFA levels in lambs. Additionally, it may be said that the risk of coronary heart diseases may decrease in humans who consume the offal of lambs fed with alfalfa.
Utjecaj lucerne i koncentriranih krmiva na razinu kolesterola i sastav masnih kiselina u serumu i iznutricama janjadi
Keywords: alfalfa; fatty acid; cholesterol; lamb; serum; offal